Uncovering the managerial dimensions of chemistry laboratory management: An exploratory factor analysis in senior high schools of the border region of West Kalimantan - Rody Putra Sartika; Lukman Hadi; Natalino Parada (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2026)
Effective chemistry laboratory management is fundamental to supporting meaningful laboratory-based learning; however, empirical evidence validating the structural relationships among managerial dimensions remains limited, particularly in geographically disadvantaged regions. This study employed Exploratory Factor Analysis (EFA) to identify and validate the underlying managerial dimensions of chemistry laboratory management in senior high schools located in the border region of West Kalimantan, Indonesia. Data was collected from 99 chemistry teachers using a Guttman-scale questionnaire measuring five managerial dimensions: planning, organizing, actuating, monitoring, and evaluation. The Kaiser–Meyer–Olkin (KMO) value of 0,807 and a significant Bartlett's Test of Sphericity (χ² = 261,424, p < 0,001) confirmed the suitability of the data for factor analysis. Principal Component Analysis extracted one component with an eigenvalue of 3,210, explaining 64,208% of the total variance. Planning (0,936) and organizing (0.877) demonstrated the highest loading factors, whereas actuating showed the lowest loading (0,552). These findings indicate that planning and organizing represent the core managerial dimensions underpinning effective chemistry laboratory management, while the implementation of laboratory activities varies across schools. The findings highlight the need to strengthen systematic planning, organizational coordination, and integrated laboratory management systems to improve sustainable laboratory governance. This study provides empirical evidence that supports the development of laboratory management policies and practices, particularly for secondary schools in geographically disadvantaged border regions.